1998
DOI: 10.1063/1.366949
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in tin-doped indium oxide thin films prepared by sol-gel technique

Abstract: Hall effect measurements have been performed on tin-doped indium oxide thin films prepared by the dipping method. The apparent variation of electron mobility with carrier concentration in these films has been quantitatively interpreted in terms of scattering at charged and neutral impurities. An electrical resistivity as low as 3.2×10−4 Ω cm was obtained for the films doped with about 6 at. % Sn. A further increase in the doping content lead to the formation of neutral defects without contributing carriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…For the air-annealed ITO thin films, an increase in Sn concentration of up to 15 at.% near the grain boundaries compared to 5 at.% in the bulk was reported by Morikawa et al 30 Since the solubility limit of Sn in In 2 O 3 is around 6-9 at.%, 16,22,[31][32][33] to phases such as SnO 2 or In 4 Sn 3 O 12 . 22,31 The formation of intergranular amorphous phases with high concentration of neutral dopants was also reported.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…For the air-annealed ITO thin films, an increase in Sn concentration of up to 15 at.% near the grain boundaries compared to 5 at.% in the bulk was reported by Morikawa et al 30 Since the solubility limit of Sn in In 2 O 3 is around 6-9 at.%, 16,22,[31][32][33] to phases such as SnO 2 or In 4 Sn 3 O 12 . 22,31 The formation of intergranular amorphous phases with high concentration of neutral dopants was also reported.…”
Section: Resultsmentioning
confidence: 75%
“…It is believed that these large surface states result from the crystallographic as well as the compositional disorder such as a higher free volume, Sn segregation 30 and oxidation 22,31,32 near the grain boundaries. For instance, Gassenbauer et al 26 have reported a direct relation between the surface states and the Sn concentration for the ITO thin films.…”
Section: Resultsmentioning
confidence: 99%
“…This table clearly shows that scattering by grain boundaries apparently play a subordinate role in the present films since the carrier mean free path is considerably shorter than the average crystallite. Radhouane et al 19,26 have demonstrated that the behavior of the electron mobility in sol-gel coated AZO films can be interpreted in terms of neutral and ionized impurity scattering. Kim et al 27 reported that the carrier concentration decreases from 7.5 × 10 20 /cm 3 for the AZO sputtered film prepared with the 3 wt.% Al 2 O 3 target to ∼2.4 × 10 20 /cm 3 for sample prepared with the 5 wt.% Al 2 O 3 target.…”
Section: Electrical Characteristicsmentioning
confidence: 98%
“…Due to its high transmittance and good physical and chemical properties [1,2], it is widely used in optical devices like flat panel displays, solar cells, sensors, and so on [3][4][5]. There are many different methods for the fabrication of ITO thin films including the magnetron sputtering method [6,7], thermal evaporation method [8], plasma ion-assisted evaporation [9], reactive electron-beam evaporation [10], and sol-gel method [11]. It is well known that almost all thin films, produced by the various deposition techniques, have residual stresses.…”
Section: Introductionmentioning
confidence: 99%